Becoming a bilingual teacher in a Chinese university: a case study. Issue 5 (2nd September 2016) - Ai, Bin
Abstract: Higher education in China has developed significantly over the past decades. Many universities have established cooperative partnerships with western universities, and overseas courses are being progressively introduced to China. At many Chinese universities, a cohort of teachers endeavor to open up bilingual subjects as a bridge to their students' future learning; accordingly, there are higher expectations of the teachers involved in bilingual education and challenges for their professional development. In this case study, the researcher invites a Chinese professor to reflect on his experiences of bilingual instruction at a university situated in central China. After describing how the bilingual course in the case study was set up and the difficulties confronted, this study uses theories of hybrid identity and third space to contextualize how bilingual teachers experience hybrid identity construction and transformation in their adaptation to the new challenges. This in-depth study will shed light on the professional development of bilingual teachers in China's higher education industry.